Evaluating student’s preferences for university brands through conjoint analysis and market simulation - Kamal Basha, Norazlyn; Sweeney, Jillian C.; Soutar, Geoffrey Norman (Emerald Publishing, 2019)
Purpose In recent times, many universities have been pressured to become heavily involved in university branding. The purpose of this paper is to investigate students’ perceptions of different international universities (brands) in terms of important university attributes, including the country in which the university’s main campus is located and educational programs are designed (COD) and the method by which the educational services are distributed internationally (DM).